Gill regeneration in the mayfly Cloeon uncovers new molecular pathways in insect regeneration - Carlos A. Martin-Blanco; Pablo Navarro; José Esteban-Collado; Florenci Serras; Isabel Almudi; Fernando Casares (Open Biology)
The capacity to regenerate lost organs is widespread among animals, and yet the number of species in which regeneration has been experimentally probed using molecular and functional assays is very small. This is also the case for insects, for which we still lack a complete picture of their regeneration mechanisms and the extent of their conservation. Here, we contribute to filling this gap by investigating regeneration in the mayfly Cloeon dipterum. We focus on the abdominal gills of Cloeon nymphs, which are critical for osmoregulation and gas exchange. After amputation, gills re-grow faster than they do during normal development. Direct cell count and EdU assays indicate that growth acceleration involves an uniform increase in cell proliferation throughout the gill, rather than a localized growth zone. Accordingly, transcriptomic analysis reveals an early enrichment in cell cycle-related genes. Other gene classes are also enriched in regenerating gills, including protein neddylation and other proteostatic processes. We then showed the conservation of these mechanisms by functionally testing protein neddylation, the activin signalling pathway or the mRNA-binding protein Lin28, among other genes, in Drosophila larval/pupal wing regeneration. Globally, our results contribute to elucidating regeneration mechanisms in mayflies and the conservation of mechanisms involved in regeneration across insects.